2020
DOI: 10.1186/s12864-020-06989-x
|View full text |Cite
|
Sign up to set email alerts
|

Using short read sequencing to characterise balanced reciprocal translocations in pigs

Abstract: Background: A balanced constitutional reciprocal translocation (RT) is a mutual exchange of terminal segments of two non-homologous chromosomes without any loss or gain of DNA in germline cells. Carriers of balanced RTs are viable individuals with no apparent phenotypical consequences. These animals produce, however, unbalanced gametes and show therefore reduced fertility and offspring with congenital abnormalities. This cytogenetic abnormality is usually detected using chromosome staining techniques. The aim … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…The largest study of the applications of WGS into the study of porcine chromosome rearrangements performed short-read sequencing to seven carriers of karyotypically balanced rearrangements alongside 15 non-carriers [ 178 ]. Here, it was found that short-read sequencing was capable of accurately detecting the breakpoint junctions of six of seven carriers, with no false-positives detected.…”
Section: Implementation Of Cytogenomics In Clinical Cytogeneticsmentioning
confidence: 99%
See 4 more Smart Citations
“…The largest study of the applications of WGS into the study of porcine chromosome rearrangements performed short-read sequencing to seven carriers of karyotypically balanced rearrangements alongside 15 non-carriers [ 178 ]. Here, it was found that short-read sequencing was capable of accurately detecting the breakpoint junctions of six of seven carriers, with no false-positives detected.…”
Section: Implementation Of Cytogenomics In Clinical Cytogeneticsmentioning
confidence: 99%
“…Here, it was found that short-read sequencing was capable of accurately detecting the breakpoint junctions of six of seven carriers, with no false-positives detected. The main deficiency of short-read sequencing noted was that it was not capable of identifying breakpoint junctions occurring in repetitive sequences [ 178 ]. This study for the first time described the breakpoints of chromosome rearrangements in the pig genome, identifying several varieties of breakpoint signatures including microhomology, microinsertions, and blunt-end ligations also characteristic of human rearrangement breakpoint junctions [ 156 , 178 ].…”
Section: Implementation Of Cytogenomics In Clinical Cytogeneticsmentioning
confidence: 99%
See 3 more Smart Citations